Functional Movement Screeningand injury risk in elite adolescentrugby league players - Dyer, C. S.; Callister, R.; Sanctuary, C. E.; Snodgrass, S. J. (International Journal of Sports Science & Coaching, 2019)
Research is limited as to whether Functional Movement Screen scores relate to non-contact injury risk in rugby league players. This cohort study investigates whether the Functional Movement Screen score predicts non-contact injuries in elite adolescent rugby league players. Australian adolescent rugby league players (n = 52; mean age 16.0 ± 1.0 years) from one club participated in this study. Functional Movement Screen scores, height, and mass were collected at the beginning of the preseason. Training, match exposure, and injury incidence data (non-contact match and training injuries with three levels of severity) were recorded for each individual athlete throughout the season. Linear and logistic regression analyses were conducted to investigate the association between Functional Movement Screen score (continuous score, = 14 or > 14, and three subscores) and injury risk, whilst controlling for exposure time. The mean Functional Movement Screen score for the sample was 13.4 (95% CI: 11.0-14.0). A total of 72 non-contact injuries were recorded (incidence rate: 18.7 per 1000 exposure hours; 95% CI: 11.6-24.8). There were no statistically significant associations between non-contact injury and Functional Movement Screen score for any of the analyses conducted. Our results suggest that the Functional Movement Screen does not reflect non-contact injury risk in elite adolescent rugby league players. Further research should investigate whether a more sport-specific movement screen in the preseason can more effectively predict injury risk in this population.